DGMATH Berbasis Augmented Reality Sebagai Inovasi Media Pembelajaran di Era Digital - Yuniarti, Dwi Ariani Finda; Abadi, Fajar; Munir, Mochamad Syahrul; Fu'adi, Anwar; Hikmahwan, Bagus (Edumatica : Jurnal Pendidikan Matematika, 2024)
The use of technology-based media can support students' creativity and optimize their learning outcomes, especially in mathematics, where many students often face difficulties. DGMATH AR is an augmented reality (AR)--based mathematics learning media designed to bring virtual animations into the real world in alignment with the learning material. This study aims to design AR-based learning media. The material used focuses on the properties of solid shapes for second-grade elementary school students. This research is a quantitative descriptive study involving users of the learning media, including teachers, students, and parents, as the subjects. The method employed is the Multimedia Development Life Cycle (MDLC), which consists of six stages: concept, design, material collection, assembly, testing, and distribution. The instrument used was a questionnaire based on the USE Questionnaire, comprising 30 statements grouped into four dimensions: usefulness, ease of use, ease of learning, and satisfaction. The questionnaire was administered to 100 respondents. The results of the USE Questionnaire showed scores of 81.12% for usefulness, 82.25% for ease of use, 82.31% for ease of learning, and 80.11% for satisfaction. Thus, it can be concluded that the AR-based DGMATH is highly suitable for use as mathematics learning media in the digital era.